WAM and WAVEWATCH-III intercomparison studies in the North Indian Ocean using Oceansat-2 Scatterometer winds. (August 2019) - Swain, J; Umesh, PA; Balchand, AN
This paper presents the intercomparison of wave hindcasts using the third-generation models WAM and WAVEWATCH-III for the North Indian Ocean over 1° × 1° (latitude × longitude) grid resolutions, which reveals the first assessment of their relative performance through intercomparison of the model results. Hindcast wave parameters such as significant wave height, mean wave period, and swell wave height obtained from the simulations using Oceansat-2 scatterometer winds are analyzed to understand the quality and variability associated with the individual model outputs in the Indian Ocean. WAM and WAVEWATCH-III intercomparison studies are carried out for four different cases (January and June 2010, and January and June 2011). A comparative study of the relative performances of these two models is evaluated through extensive and robust statistical error analysis. Based on both qualitative and quantitative assessment of the model results, this study clearly indicates that both WAM and WAVEWATCH-III performed well in the common model domain using Oceansat-2 scatterometer winds, and they can be confidently used for long-term hindcasting in the North Indian Ocean, which will be very useful for most of the user community dealing with various coastal/offshore activities. The study also suggests that it would be preferable to consider available long-term wave measurements both in deep and coastal waters of the North Indian Ocean to validate and intercompare WAM and WAVEWATCH-III further.